2016
DOI: 10.4187/respcare.04729
|View full text |Cite
|
Sign up to set email alerts
|

A Preventative Respiratory Protocol to Identify Trauma Subjects at Risk for Respiratory Compromise on a General In-Patient Ward

Abstract: Study results suggest that a preventive respiratory protocol had a beneficial effect on patient outcomes; receiving the protocol reduced hospital days and eliminated unplanned admission to the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…All 28 studies demonstrated cost savings. The included studies covered a wide variety of respiratory care practices, which included the topics of ventilators (9); [16][17][18][19][20][21][22][23][24] multiple therapies (7); [25][26][27][28][29][30][31] disease management (4); [32][33][34][35][36] invasive procedures (3), [line insertion (2) for arterial 37 and internal jugu- 40,41 and oxygen (2). 42,43 Sixteen of the studies (57%) utilized protocols.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 28 studies demonstrated cost savings. The included studies covered a wide variety of respiratory care practices, which included the topics of ventilators (9); [16][17][18][19][20][21][22][23][24] multiple therapies (7); [25][26][27][28][29][30][31] disease management (4); [32][33][34][35][36] invasive procedures (3), [line insertion (2) for arterial 37 and internal jugu- 40,41 and oxygen (2). 42,43 Sixteen of the studies (57%) utilized protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies were conducted in acute critical-care settings (11) [16][17][18][19][20][22][23][24][37][38][39] or acute non-ICU settings (13). 21,[25][26][27][28][29][30][31][33][34][35]40,41 There were 3 studies conducted in ambulatory care, 32,36,42 and 1 study was conducted in a long-term care setting. 43 Most studies addressed the adult population (24), with 2 each studying pediatric 32,34 and neonatal populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Nyland et al 7 in this issue of RESPIRATORY CARE highlights several important aspects of this effort. First is the importance of recognizing risk factors among patients who otherwise may not have been at risk of respiratory failure and instituting a program of increased vigilance and proactive measures to identify and mitigate risk factors for respiratory embarrassment and resultant complications.…”
Section: See the Original Study On Page 1580mentioning
confidence: 97%